Penanganan Stunting Melalui Program Pemberdayaan Masyarakat - Nurwijayanti Nurwijayanti; Agustin Widyowati; Reza Fahrepi (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Stunting is a public health issue that is a top priority in Indonesia's national development. The objective of this community service program is to implement a community empowerment program to address stunting. Implementing a community empowerment program to address stunting through a social and economic approach provides significant benefits for various parties, both in the short and long term, as supported by various empirical studies and theoretical frameworks for sustainable development. The approaches used in this service include community-based participatory action, an adult learning approach, a train-the-trainer model, and a cascade training method. The implementation stages of the activity began with coordination with stakeholders, baseline surveys and pre-assessments, development of training materials, provision of training materials, and finally, evaluation. This community service was attended by 33 participants from community companion cadres in Tanah Grogot District, Paser Regency under the working area of the Department of Population Control, Family Planning, Women's Empowerment and Child Protection (PPKBPPPA) of Paser Regency. The results of the community service showed that the socialization activities were effective in increasing the knowledge of stunting companion cadres about stunting and their role in stunting prevention, with an average increase in score of 52.6% (p <0.001). The distribution of knowledge experienced a positive shift from the majority in the poor category (54.5%) to the majority in the good category (69.7%). The basic knowledge material on stunting experienced the highest increase (58.1%), followed by the material on the role of cadres (46.7%). The active learning method used proved effective in increasing the understanding of cadres.